PERMASALAHAN AIRTANAH PADA DAERAH URBAN - Triadi Putranto, Thomas; Indra Kusuma, Kristi (Diponegoro University, 2009)
Groundwater is one of water resources that can be exploitated to supply human being basic need becauseof its quality and quantity. Groundwater overexploitation can give negative impact to environmentalequilibrium. Human activities such as groundwater overexploitation, civilization problems, coastreclamation and industrial area developments can give groundwater problems in urban area. Groundwaterproblems that can be happened such as surface flooding, sea water intrusion, land subsidence andgroundwater pollution as the impact of human activities. Mitigations that can be conducted to minimizenegative impact of groundwater overexploitation are by technical and nontechnical programs